IMPROVING LITERAL AND INFERENTIAL COMPREHENSION USING KNOW-WHAT TO LEARN-LEARNED (KWL) STRATEGY - Erliana, Santi (English Department of Faculty of Tarbiyah and Teachers Training, 2014)
This paper highlights the findings of a study which was undertaken at the Institute for Islamic Studies (hencefort STAIN) of Palangka Raya. The aim of the study was to describe how the teaching of reading using reading strategy Know-What to learn-Learned (henceforth K-W-L) strategy can improve reading comprehension for the fifth semester students of the English education study program in STAIN Palangka Raya in academic year 2013/2014. 26 fifth semester students from English education study program were taken as the subject of the study. The data were taken from observation, field notes, questionnaire, and achievement test. The result reveals that the K-W-L not only improves comprehension but also increase motivation in learning.